MIFTAH’s Digital Diplomacy in the Struggle of Palestinian Women (Universitas Terbuka, 2025)
The Israeli occupation of Palestine has caused significant suffering for women. The government's efforts to address this issue have been carried out by initiating a National Action Plan, which is an adoption of WPS UNSCR 1325. The government's efforts, which are perceived as unsuccessful, have led to the emergence of several non- governmental organizations, such as MIFTAH (The Palestinian Initiative for the Promotion of Global Dialogue and Democracy). The purpose of this study is to examine MIFTAH's efforts to fight for Palestinian women using digital diplomacy. Using descriptive research techniques, data was collected secondarily. Data collection techniques were carried out through library research and digital diplomacy as an analytical tool. The results show that MIFTAH's advocacy through social media (website, Twitter, and Instagram) has been carried out, although it still faces various problems, including technological limitations, disinformation caused by Western propaganda or hasbara, and dependence on digital media trends that are temporary and unsustainable. Nevertheless, MIFTAH's digital efforts continue to make an important contribution to the struggle for Palestinian women. MIFTAH's digital diplomacy is a relevant alternative for Palestine.